POLA FRAUD PADA PENYELENGARAAN BIMBINGAN TEKNIS (BIMTEK) DI SEKTOR PEMERINTAHAN - Indah Sri Wahyuni; - Tarjo (JAFFA, 2016)
This study is aims to determine patterns of fraud in the technical assistance implementation activities in the government sector that is in the local work unit in the district X. It’s descriptive qualitative study by interviewing several informants who where directly involved in the technical assistance.The aspects that will be analyzed include three phases: planning phases, implementation phases and reporting phase. The result of this study shows that the frauds in the  three phase of technical assistance implementation. There are mark up of the price and number of participants at the planning phase. In the implementation phase the fraud is within shortening timing and eventually there is technical assistance fictitious, and at the reporting phase found that the fraud pattern is a discrepancy between the letter of accountability with real cost.